2022
DOI: 10.1007/jhep11(2022)005
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping conformal QED3 and deconfined quantum critical point

Abstract: We bootstrap the deconfined quantum critical point (DQCP) and 3D Quantum Electrodynamics (QED3) coupled to Nf flavors of two-component Dirac fermions. We show the lattice and perturbative results on the SO(5) symmetric DQCP are excluded by the bootstrap bounds with an assumption that the lowest singlet scalar is irrelevant. Remarkably, we discover a new family of kinks in the 3D SO(N) vector bootstrap bounds with N ⩾ 6. We demonstrate coincidences between SU(Nf) adjoint and $$ \textrm{SO}\left({N}_f^2-1\right)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For instance, QED 3 with N f fermions is believed to stop being conformal below some N crit f . It has been difficult to precisely bootstrap this theory [35][36][37][38][39]. It is possible that a sharp signature for this theory could be found by bootstrapping a large set of correlators, which could be made feasible using our method.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, QED 3 with N f fermions is believed to stop being conformal below some N crit f . It has been difficult to precisely bootstrap this theory [35][36][37][38][39]. It is possible that a sharp signature for this theory could be found by bootstrapping a large set of correlators, which could be made feasible using our method.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known since [20] 3D, the O(N ) vector bootstrap bounds show sharp kinks (type I) which are saturated by the 3D critical O(N ) vector models. Moreover, in [21] the author observed that besides the type I kinks, the 3D O(N ) vector bootstrap bounds also show another family of kinks (type II) which approach the free fermion bilinear in the large N limit. The type II kinks appear in general dimensions [18], and the kink in Fig.…”
Section: O(n ) Vector Crossing Equations In 1dmentioning
confidence: 99%
“…For instance, the 3D O(N ) vector bootstrap bounds have two types of kinks [20,21]. The type I kinks with an O(N ) vector scalar φ near a free boson ∆ φ = 1 2 are related to the critical O(N ) vector model [20], while the type II kinks with ∆ φ near free fermion bilinears also appear in general dimensions and show close relation with conformal gauge theories [18,21].…”
Section: Introductionmentioning
confidence: 99%